Governance, Climate Change and Migration in The Upper West Region of Ghana - Seyram, R. (University of Ghana, 2023)
While literature is replete with studies on the role of governance (national policies and local institutions) in shaping the impacts of climate change on livelihoods and adaptation practices globally, scanty attention is, however, given to how national policies and local institutions shape climate-induced migration. This study, therefore, examined the possible links between national policies and local institutions, climate change and its impacts on livelihoods and migration in the Wa West District and the Jirapa Municipality of the Upper West Region of Ghana. The study relied on the Structuration theory and the Department for International Development (DFID) Sustainable Livelihood Framework to analyse the relationship between governance (national policies and local institutions), climate change and migration. Using the Sequential Explanatory Mixed Methods approach, the study employed a three-stage stratified sampling design to select 300 households from six communities in the Wa West District and the Jirapa Municipality. Focus group discussions, in-depth interviews and key informant interviews were used to obtain information from both respondents and heads of institutions. The findings indicated that the combined effect of climate and non-climate related hazards such as irregular rains, drought and declining soil fertility adversely affected crop farming and other livelihood sources of households in the study areas. The study again showed that households used seasonal migration as a strategy to deal with the negative effects of climate change on their livelihoods. For migration as an adaptation strategy, the role of migrant remittances was found as crucial. It was discovered that most economic migration were implicitly fueled by climate and environmental factors. The findings further revealed that national policies such as National Fertiliser Subsidy Programme, One-Village-One-Dam, One-District-One-Factory and the Savanna Accelerated Development Authority; and local institutions such as traditional land tenure system, family and friends (informal actors), Non-Governmental Organisations, and Agriculture Extension Services are not enhancing livelihoods of households hence, outmigration in the region is still being amplified as households need to diversify livelihoods. The study, on the account of these findings concludes that, despite the adverse impact of climate change on livelihoods, and the fact that migration is increasingly being used as a coping and an adaptation strategy to deal with this, governance (national policies and local institutions) is insignificantly shaping these contexts. The study, therefore, recommends that the National Development Planning Commission, Ministry of Environment, Science, Technology and Innovation, Ministry of Food and Agriculture, Ministry of Foreign Affairs and Regional Integration, Ministry of the Interior and the Migration Unit should collaborate and formulate a comprehensive policy and institutional framework that address climate-induced migration. Alternatively, the Ministry of Foreign Affairs and Regional Integration, the Ministry of the Interior and other agencies such as the Migration Unit should facilitate the establishment of the Ghana National Migration Commission to further trigger the operation of the National Migration Policy, which is expected to regulate all aspects of migration.
PhD. Migration Studies
Keywords: literature; governance; Upper West Region of Ghana; Wa West District